Новітні рекламні технології, що змінюють підходи до рекламної стратегії - Кітченко, Олена Миколаївна; Мірошник, Марія Володимирівна (Дніпропетровський державний аграрно-економічний університет, 2024)
В статті розглядаються питання пов’язані з особливостями застосування новітніх рекламних технологій сучасними компаніями. Встановлено, що новітні рекламні технології наразі змінюють традиційні підходи до розробки та використання рекламної стратегії, а також є більш орієнтованими на кожного окремого споживача. Визначено, що сучасне висококонкурентне ринкове середовище підштовхує компанії використовувати новітні рекламні рішення для досягнення нового маркетингового ландшафту. В статті надаються характеристики найбільш затребуваних традиційних рекламних технологій, розглядаються їх особливості, переваги та недоліки в контексті сучасної України. Проаналізовані особливості та порядок застосування штучного інтелекту, віртуальної реальності, аналітики даних та інших інноваційних засобів у підвищенні ефективності рекламних кампаній. Наведено приклади реалізації таких технологій українськими підприємствами в своїй рекламній діяльності. Розглянуто вплив персоналізації реклами, розумних алгоритмів таргетингу та інтерактивних форматів на сприйняття аудиторією реклами. В статті також розглядаються етичні аспекти використання цих технологій та можливі наслідки для суспільства і рекламодавців. Висновки дослідження вказують на те, що інноваційні рекламні технології відкривають нові можливості для залучення аудиторії, формування рекламних стратегій та підвищення конкурентоспроможності брендів у сучасному цифровому середовищі.

The article deals with the issues related to the peculiarities of application of the latest advertising technologies by modern companies. It is established that the latest advertising technologies are currently changing the traditional approaches to the development and use of advertising strategy, and are more focused on each individual consumer. It becomes clear that today's highly competitive market environment is pushing companies to use the latest advertising solutions to achieve a new marketing landscape. Changes in today's globalised space have led to changes in many aspects of human activity: innovation, culture, changes in traditional business approaches, changing consumer tastes and demands, etc., all of which have led to a shift from traditional channels and technologies for distributing advertising messages to the latest ones. The article describes the characteristics of the most popular traditional advertising technologies, considers their features, advantages and disadvantages in the context of modern Ukraine. The article defines the terms traditional and new advertising technologies. The gradual transition from traditional to new advertising technologies is emphasised. Statistical data on the rate of use of these technologies in the world and their further development are provided. The article analyses the peculiarities and procedure of using artificial intelligence, virtual reality, data analytics and other innovative tools to increase the effectiveness of advertising campaigns. Examples of the implementation of such technologies by Ukrainian enterprises in their advertising activities are provided. The article examines the impact of advertising personalisation, smart targeting algorithms and interactive formats on the audience's perception of advertising. The article also discusses the ethical aspects of using these technologies and the possible consequences for society and advertisers. The conclusions of the study indicate that innovative advertising technologies open up new opportunities for attracting audiences, developing advertising strategies and increasing the competitiveness of brands in the modern digital environment.
The latest advertising technologies that change approaches to advertising strategy
Keywords: рекламні технології; стратегія; просування; інтернет; штучний інтелект; реклама; advertising technologies; strategy; promotion; Internet; artificial intelligence; advertising